Updated Definition of the Three Solvent Descriptors Related to the Van der Waals Forces in Solutions - Laffort, Paul (Scientific Research, 2018)
Innovative viewpoint on the older topic of the van der Waals forces, is of interesting and significant issue to be concerned in both the fields related to the fundamental investigation and thus valuable in guiding the new physiochemical phenomena and processes for both academic research and practical applications. The intermolecular Van der Waals forces involved in solutions have been recently deeply reconsidered as far as the solute side is concerned. More precisely, the solute descriptors (or parameters) experimentally established, have been accurately related to molecular features of a Simplified Molecular Topology. In the present study, an equivalent result is reached on the solvent side. Both experimental parameters have been obtained simultaneously in previous Gas Liquid Chromatographic studies for 121 Volatile Organic Compounds and 11 liquid stationary phases, via an original Multiplicative Matrix Analysis. In that experimental step, five groups of forces were identified, two of hydrogen bonding and three of Van der Waals: 1) dispersion (London), 2) orientation or polarity strictly speaking (Keesom), and 3) induction-polarizability (Debye). At this stage, an attempt of characterization the solvent parameters via the SMT procedure has been limited to those related to the Van der Waals forces, those related to the hydrogen bonding being for now left aside.
Keywords: Van der Waals Intermolecular Forces; Solvent Descriptors; Gas Liquid Chromatography; Chemo Informatics; Multiplicative Matrix Analysis